2018
DOI: 10.1371/journal.pone.0201944
|View full text |Cite
|
Sign up to set email alerts
|

Thyromental height test as a new method for prediction of difficult intubation with double lumen tube

Abstract: BackgroundPredicting difficult intubation is of high clinical interest.Methods237 patients aged ≥18 years were included in the study. Preoperative airway evaluation included: Mallampati test, thyromental distance, sternomental distance and thyromental height test. During direct laryngoscopy Cormack & Lehane classification was graded. We calculated the ROC AUC, sensitivity and specificity for thyromental height test as a primary end point of our study.ResultsOnly thyromental height test and Cormack-Lehane scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 23 publications
(27 reference statements)
4
16
0
Order By: Relevance
“…In our study, SMD sensitivity was found to be 53.3%, speci city was 86.2%, PPV was 28.6%, NPV was 94.7%, and accuracy was 83.1%. These ndings are consistent with the results of Palczynski et al [40], who found a sensitivity of 60% and a PPV of 19% for SMD. A poor sensitivity and PPV for this test (8.3% and 3.4%, respectively) were observed by Khatiwada et al [41] and, in a study by Shobha et al [42], SMD sensitivity was found to be 3.3% and PPV was 6.25%.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, SMD sensitivity was found to be 53.3%, speci city was 86.2%, PPV was 28.6%, NPV was 94.7%, and accuracy was 83.1%. These ndings are consistent with the results of Palczynski et al [40], who found a sensitivity of 60% and a PPV of 19% for SMD. A poor sensitivity and PPV for this test (8.3% and 3.4%, respectively) were observed by Khatiwada et al [41] and, in a study by Shobha et al [42], SMD sensitivity was found to be 3.3% and PPV was 6.25%.…”
Section: Discussionsupporting
confidence: 93%
“…Bindra et al [39], however, found no signi cant changes in the diagnostic performance of the MMT-TP in the sitting or the supine positions. SMD is anatomically easy to measure and is commonly used in clinical practice [40].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in airways adjuncts like the introduction of videolaryngoscopes into clinical practice have led to fewer life-threatening complications, however the risk of serious complications still remains. Despite protracted convalescent, the current definitions to predict difficult airway situations are inadequate and often times prove unchallenging [3,4]. Conversely, unanticipated difficult airway scenarios occur when least expected and significantly lead to anesthesia-related morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al [35] demonstrated that the Mallampati test correctly depicts di cult intubations when the test is performed without phonation. SMD is anatomically easy to measure and is commonly used in clinical practice [40].…”
Section: Discussionmentioning
confidence: 99%